Customer Retention of Using Mobile Banking a Case Study of One of the Largest Bank in Thailand - Kacharoen, Nitchaya; Thanabordeekij, Pithoon (INTERNATIONAL SCIENTIFIC JOURNAL OF ENGINEERING AND TECHNOLOGY (ISJET), 2019)
This research is focused more on the customer retention of using mobile banking service in Thailand i.e. a case study of one of the largest bank in Thailand. The study has combined personality dimensions of Technology Readiness Index and cognitive dimensions of Technology Acceptance Model with antecedents such as consumer satisfaction and loyalty to provide robust framework of mobile banking adoption process. Also the study examines the influencing factors that determine the customer loyalty for ABC mobile banking application. The Inferential Analysis was done to test the validation of the technology readiness and acceptance model (TRAM) constructs and their interrelationship among each other. The finding reveals that TRAM variables have a significant influence on use of ABC Bank Mobile application in Bangkok. The study concludes with a discussion on practical implications of the research across similar service providers within the industry.